MANAJEMEN KRISIS PUBLIC RELATIONS PONDOK PESANTREN DALAM MERESPON ISU RADIKALISME DAN TERORISME (Studi Kasus Pada Pondok Pesantren Nurussalam Desa Kujang Kabupaten Ciamis) - Saiful Romadon; Ade Budi Santoso (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research uses the Image Restoration theory from William L. Benoit. The research paradigm used is constructivism with a qualitative research approach and a particular case study method that focuses on events, situations, phenomena, and special programs of Nurussalam Islamic Boarding Schools in responding to issues. The research data were obtained by in-depth interview technique with Key Informants who were inside Nurussalam Islamic Boarding School and other trusted informants. The results of this study indicate that the Public Relations efforts at Nurussalam Islamic Boarding School have succeeded in convincing the public that Nurussalam Islamic Boarding School has never been involved in a series of acts of terrorism in Indonesia. The indications can be seen in the results of interviews with the head of the RT and local residents, that at this time the relationship between Nurussalam Islamic Boarding School and the surrounding community is very harmonious. Public Relations Efforts Nurussalam Islamic Boarding School by carrying out activities that always involve the surrounding community, in terms of holding social services such as mass circumcision, free medical treatment, and commemoration of Islamic holidays.